Perovskite type lanthanum manganate bimetallic doped catalyst and preparation method thereof

By using perovskite lanthanum manganate bimetallic doping catalyst in metal-air batteries, the problems of insufficient catalyst activity and structural stability are solved, and efficient oxygen reduction reaction and excellent battery performance are achieved, which is suitable for industrial mass production.

CN119890335APending Publication Date: 2025-04-25CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510116422.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In existing metal-air batteries, there is insufficient catalyst activity, high charging overpotential, poor low-temperature conductivity, and A/B doping will have adverse effects on the catalyst structure.

Method used

Perovskite-type lanthanum manganate bimetallic doping catalyst is used to perform cation doping at the A and B positions of the perovskite material at the same time. The specific molecular formula is La0.9Ce0.1CoxMn1-xO3, x is a non-negative real number, 0≤x≤0.4. The catalyst ensures uniform distribution of doped elements and structural stability of the catalyst through specific preparation methods, including salt solution mixing, calcining and other steps.

Benefits of technology

The half-wave potential and ultimate diffusion current density of the catalyst are improved, so that the number of electrons transferred in the reaction is close to the ideal four-electron reaction path, and the catalyst exhibits efficient oxygen reduction reaction selectivity in metal-air batteries, with the yield of by-product hydrogen peroxide being less than 0.23%. At the same time, the performance indicators of zinc-air batteries and magnesium-air batteries have been significantly improved, including open circuit voltage and power density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890335A_ABST
    Figure CN119890335A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite type lanthanum manganate bimetallic doped catalyst and a preparation method, the molecular formula of the catalyst is La0. 9Ce0. 1CoxMn1-xO3, x is a non-negative real number, and x is more than or equal to 0 and less than or equal to 0.4; the catalyst can be used as a catalyst for a metal-air battery. A / B site metal double doping of LaMnO3 is realized by adopting a simple sol-gel and high-temperature calcination method, and the perovskite type lanthanum manganate double-metal doped catalyst which is large in specific surface area, porous, loofah-shaped and high in oxygen reduction performance is synthesized. According to the catalyst, the catalytic performance of the oxygen reduction reaction of the metal-air battery is improved, the limit diffusion current density is 1.2 times that of commercialized Pt / C. The preparation raw materials of the catalyst are easy to obtain, the preparation method is simple, the cost is low, and the catalyst has a potential commercialized application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage technology, and in particular to a perovskite-type lanthanum manganate bimetallic doped catalyst and a preparation method thereof. Background Art

[0002] As a special electrochemical energy storage device, metal-air batteries combine the design features of traditional batteries and certain characteristics of fuel cells. In its design, metal is used as the negative electrode, and the porous positive electrode structure uses a continuous supply of oxygen as a reactant. This design gives metal-air batteries a very high energy density, which is about 2 to 10 times that of lithium-ion batteries. Taking zinc-air batteries as an example, due to the abundant reserves of zinc, low prices, and a theoretical voltage of 1.65V and a theoretical energy density of 1.36kWh·kg -1 (about 5 times that of lithium-ion batteries). It is not only environmentally friendly and non-toxic, but also regarded as a promising new energy device, and has received extensive attention and research. Similarly, magnesium-air batteries have also attracted widespread attention and research due to their low cost, clean and safe, and higher theoretical discharge voltage (3.1V) and energy density (6.8kWh·kg -1 ), showing great application potential in portable electronic devices, marine underwater instruments and backup energy.

[0003] However, despite the many advantages of metal-air batteries, their large-scale commercial application is limited by some technical challenges, especially the slow kinetics of the positive electrode oxygen reduction reaction (ORR). The ideal ORR process needs to go through a four-electron reaction pathway, that is, oxygen fully participates in the reaction and is reduced. To achieve this goal, it is crucial to develop oxygen reduction catalysts with high catalytic activity. At present, commonly used oxygen reduction catalysts are mainly divided into two categories: precious metals and non-precious metals. Although precious metals such as platinum-based materials can effectively accelerate ORR kinetics, their high price, poor stability and scarcity greatly limit their widespread application. Non-precious metal catalysts include non-metallic carbon materials, metal-carbon hybrids and transition metal oxides.

[0004] As a transition metal oxide, perovskite has shown potential in the field of catalysts due to its adjustable elements, controllable activity, good stability, simple synthesis process and low cost. Perovskite materials are usually expressed as ABO3, where the A position is usually a lanthanide or alkaline earth metal element (such as La 3+ 、Sm 3+ etc.), and the B position represents a transition metal element (such as Mn, Ni, Co, Fe, Ti). In the prior art, in the perovskite LaMnO3 material, Mn 4+ / Mn 3+ The coexistence of can regulate O2 / OH -The interaction with the catalyst surface improves the ORR performance. However, LaMnO3 catalysts, like other perovskite oxides, also have problems such as high charge overpotential and poor conductivity at low temperatures.

[0005] In addition, although individual doping of the A or B site of perovskite can adjust its oxygen stoichiometry and conductivity, these also affect key factors of catalyst activity, such as the conversion of lattice oxygen, surface adsorbed oxygen, and the electronic structure of the material. These problems together constitute an important obstacle to the further development of metal-air batteries. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a perovskite-type lanthanum manganate bimetallic doped catalyst and a preparation method. The present invention performs cation doping on the A and B positions of the perovskite-type material without destroying the perovskite crystal structure, so as to solve the problems of insufficient catalyst activity, high charge overpotential, poor low-temperature conductivity, and adverse effects of A / B position doping on the catalyst structure in the prior art metal-air batteries.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A perovskite-type lanthanum manganate bimetallic doped catalyst, the molecular formula of the catalyst is La 0.9 Ce 0.1 Co x Mn 1-x O3, wherein x is a non-negative real number and 0≤x≤0.4; the catalyst can be used as a catalyst for a metal-air battery.

[0009] Preferably, the catalyst is La 0.9 Ce 0.1 MnO3、La 0.9 Ce 0.1 Co 0.1 Mn 0.9 O3, La 0.9 Ce 0.1 Co 0.2 Mn 0.8 O3, La 0.9 Ce 0.1 Co 0.3 Mn 0.6 O3, La 0.9 Ce 0.1 Co 0.4 Mn 0.6 O3.

[0010] The present invention provides a method for preparing a perovskite-type lanthanum manganate bimetallic doped catalyst, wherein the catalyst is prepared by the following steps:

[0011] Step 1: prepare salt solutions corresponding to La, Ce, Co and Mn respectively, and mix them; then add citric acid and mix evenly to obtain a mixed solution, and continuously mix the mixed solution at 50-80° C. to obtain a precursor; wherein the molar ratio of La, Ce, Co and Mn metal ions is 0.9:0.1:x:(1-x), x is a non-negative real number, and 0≤x≤0.4; the molar ratio of citric acid to the salt corresponding to La is 1:(0.8-1);

[0012] Step 2: calcining the precursor prepared in step 1 at 150-180° C. for 0.5-2 h, and then calcining at 700-900° C. for 6-10 h to obtain the catalyst.

[0013] Preferably, in step 1, the salt solution is one of nitrate, acetate or chloride.

[0014] Preferably, the salt solution is a nitrate solution; the salt solutions corresponding to La, Ce, Co and Mn are La(NO3)3·6H2O solution, Ce(NO3)3·6H2O solution, Co(NO3)2·6H2O solution and Mn(NO3)2·4H2O solution respectively.

[0015] Preferably, in step 2, the heating rate during calcination is 3°C / min.

[0016] The present invention provides a metal-air battery, wherein the positive electrode catalytic material in the battery is the above catalyst or the catalyst prepared by the above preparation method.

[0017] Preferably, the battery is a zinc / magnesium-air battery.

[0018] Preferably, in the battery, the catalytic electrode comprises a positive electrode catalytic material, a conductive carbon material, a nafion solution, anhydrous ethanol, a hydrophilic carbon paper and an air diffusion layer.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention performs a bimetallic doping treatment on the perovskite material, and simultaneously dopes different elements at the A and B positions, thereby obtaining a catalyst with a large specific surface area, a porous loofah-like microstructure, and high redox properties. The two transition metals are successfully doped without destroying the perovskite crystal structure, maintaining the integrity of the structure, and adjusting the electronic structure of the material, thereby improving the half-wave potential and limiting diffusion current density of the catalyst, so that the number of reaction transfer electrons is close to the ideal value of the four-electron reaction path in theory (greater than 3.99); at the same time, when the catalyst is used in a metal-air battery, the yield of the by-product hydrogen peroxide (H2O2) generated in the catalytic process is maintained below 0.23%, which indicates that the catalyst of the present invention has high oxygen reduction reaction (ORR) selectivity.

[0021] 2. The zinc-air battery and magnesium-air battery assembled using the catalyst of the present invention both show excellent performance. The open circuit voltage of the zinc-air battery reaches 1.5V and the power density is as high as 130mW cm -2 , with a maximum energy density of 885Wh kg ^-1 Zn The magnesium-air battery also exhibited an open circuit voltage of 1.85 V and a power of 52 mW cm -2 These performance indicators demonstrate the high efficiency and potential of the catalyst of the present invention in practical applications.

[0022] 3. The catalyst of the present invention does not contain precious metal elements, has low cost, and can be prepared by the sol-gel method, which not only ensures the excellent performance of the catalytic material, but also has high production efficiency. It solves the problem of traditional catalysts relying on expensive metals and provides a way to easily scale up production, which is suitable for industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The XRD pattern of the catalyst prepared in Example 1 is shown in FIG.

[0024] Figure 2 This is a scanning electron microscope image of the catalyst prepared in Example 1.

[0025] Figure 3 This is the open circuit voltage curve of a zinc metal air battery assembled with the catalyst prepared in Example 1 as the positive electrode.

[0026] Figure 4 The discharge polarization curve and power density curve of the zinc metal air battery assembled with the catalyst prepared in Example 1 as the positive electrode; in the figure, 1 is the discharge polarization curve, and 2 is the power density curve.

[0027] Figure 5The open circuit voltage of the magnesium metal-air battery assembled with the catalyst prepared in Example 1 as the positive electrode.

[0028] Figure 6 The discharge polarization curve and power density curve of the magnesium metal-air battery assembled with the catalyst prepared in Example 1 as the positive electrode;

[0029] In the figure, 3 is the discharge polarization curve, and 4 is the power density curve. DETAILED DESCRIPTION

[0030] The present invention will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention.

[0031] Unless otherwise indicated in specific cases in the present invention, the numerical ranges listed herein include the upper and lower limits, and all integers and fractions within the range, and are not limited to the specific values ​​listed when defining the range.

[0032] 1. A Perovskite-type Lanthanum Manganate Bimetallic Doped Catalyst

[0033] The molecular formula of the catalyst of the present invention is La 0.9 Ce 0.1 Co x Mn 1-x O3, wherein x is a non-negative real number and 0≤x≤0.4; the catalyst can be used as a catalyst for a metal-air battery. Specifically: the catalyst is La 0.9 Ce 0.1 MnO3、La 0.9 Ce 0.1 Co 0.1 Mn 0.9 O3, La 0.9 Ce 0.1 Co 0.2 Mn 0.8 O3, La 0.9 Ce 0.1 Co 0.3 Mn 0.6 O3, La 0.9 Ce 0.1 Co 0.4 Mn 0.6 One of O3.

[0034] Based on the problems existing in the prior art, the present invention considers doping and modifying the perovskite material LaMnO3 to improve its catalytic performance. The present invention chooses to use bimetallic ions for doping and modification. After in-depth research, the present invention finds that not all transition metal elements can solve the problems existing in the prior art. Because the present invention finds that the doping process also needs to consider the influence of the doping elements on the structural stability and catalytic performance of the perovskite material LaMnO3. The present invention finds that considering that Ce has a moderate ionic radius and can better adapt to the A site in the perovskite structure, other rare earth elements cannot achieve the technical effect brought by Ce. If other rare earth elements are used, the significant difference in ionic radius will cause lattice distortion, affecting the crystal structure stability of the material. At the same time, an important feature of Ce is that it can provide multiple oxidation states (Ce 3+ / Ce 4+ ), which is crucial to regulating the oxygen vacancy concentration on the catalyst surface and improving the ORR activity. The multivalent characteristics of other rare earth elements often do not have such stability, and other valence states can only be formed under specific conditions, so that the electronic structure and catalytic performance of the catalyst cannot be effectively adjusted. The selection of Co element also exists in this situation, and the transition metal Co has a rich valence state, which provides appropriate redox characteristics and charge transfer capabilities in the perovskite structure, which is very important for promoting an efficient four-electron ORR process. Moreover, different transition metal elements exhibit different chemical behaviors during high-temperature calcination, which may lead to phase separation or the formation of an undesirable second phase in the present invention, which will affect the uniformity and stability of the catalyst; at the same time, the interaction between different elements will also affect its distribution in the final product. Based on this, the present invention uses Ce and Co as doping elements, Ce can provide additional oxidation states, which helps to adjust the oxygen vacancy concentration on the catalyst surface, while Co helps to improve the charge transfer characteristics and increase the number of electron transfers; at the same time, this doping process will not damage the crystal structure of the perovskite LaMnO3, ensuring the compatibility of various elements in the catalyst and the stability of the overall structure.

[0035] 2. A method for preparing a perovskite-type lanthanum manganate bimetallic doped catalyst

[0036] Step 1: prepare salt solutions corresponding to La, Ce, Co and Mn respectively, and mix them; then add citric acid and mix evenly to obtain a mixed solution, and continuously mix the mixed solution at 50-80° C. to obtain a precursor; wherein the molar ratio of La, Ce, Co and Mn metal ions is 0.9:0.1:x:(1-x), x is a non-negative real number, and 0≤x≤0.4; the molar ratio of citric acid to the salt corresponding to La is 1:(0.8-1);

[0037] Step 2: calcining the precursor prepared in step 1 at 150-180° C. for 0.5-2 h, and then calcining at 700-900° C. for 6-10 h to obtain the catalyst.

[0038] In some embodiments of the present invention, in step 1, the molar ratio of La, Ce, Co and Mn metal ions is 0.9:0.1:x:(1-x), x is a non-negative real number, and 0≤x≤0.4. The molar ratio of each metal ion is within this range, which can ensure the completion of doping. Being lower or higher than this range will result in poor doping effect, thereby affecting the favorable improvement of the catalytic performance of the catalyst. Therefore, x can be 0, 0.1, 0.2, 0.3, 0.4, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0039] In some embodiments of the present invention, in step 1, the mixed solution is continuously mixed at 50-80°C until a stable sol-gel precursor is obtained. Therefore, the temperature during this process can be 50°C, 60°C, 70°C, 80°C, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0040] In some embodiments of the present invention, in step 1, the salt solution is one of nitrate, acetate or chloride. The salt solution is a nitrate solution; the salt solutions corresponding to La, Ce, Co and Mn are La(NO3)3·6H2O solution, Ce(NO3)3·6H2O solution, Co(NO3)2·6H2O solution and Mn(NO3)2·4H2O solution, respectively.

[0041] In some embodiments of the present invention, in step 2, the heating rate during calcination is 3° C. / min.

[0042] 3. A metal-air battery

[0043] The positive electrode catalytic material in the battery is the above catalyst or the catalyst prepared by the above preparation method. Wherein, the battery is a zinc / magnesium-air battery. In the battery, the catalytic electrode includes a positive electrode catalytic material, a conductive carbon material, a nafion solution, anhydrous ethanol, a hydrophilic carbon paper and an air diffusion layer. Wherein, the conductive carbon material is Super P, and the mass ratio of the conductive carbon material to the catalyst is 1:1.

[0044] In some embodiments of the present invention, the zinc-air battery is prepared by the following steps:

[0045] The catalyst powder was uniformly dispersed with conductive carbon material, 5wt% Nafion solution, and anhydrous ethanol by ultrasonic dispersion, and then drop-coated on hydrophilic carbon paper (so that the loading amount of the catalyst on the hydrophilic carbon paper was 1 mg cm -2 ) as the air positive electrode of the zinc metal air battery, 6M KOH aqueous solution as the electrolyte, and zinc plate as the negative electrode to assemble a zinc metal air battery.

[0046] In some embodiments of the present invention, the magnesium-air battery is prepared by the following steps:

[0047] The catalyst powder was uniformly dispersed with conductive carbon material, 5wt% Nafion solution, and anhydrous ethanol by ultrasonic dispersion, and then drop-coated on hydrophilic carbon paper (so that the loading amount of the catalyst on the hydrophilic carbon paper was 1 mg cm -2 ) as the air positive electrode of the magnesium-air battery, 10wt% KCl aqueous solution as the electrolyte, and AZ31B magnesium alloy as the negative electrode to assemble a magnesium-air battery.

[0048] 4. Embodiment

[0049] Example 1

[0050] Preparation of La 0.9 Ce 0.1 Co 0.1 Mn 0.9 O3, the specific steps are as follows:

[0051] Step 1: adding lanthanum nitrate hexahydrate, cerium nitrate hexahydrate, cobalt nitrate hexahydrate, and manganese nitrate tetrahydrate to distilled water in a molar ratio of lanthanum: cerium: manganese: cobalt ion = 0.9:0.1:0.9:0.1, stirring to obtain a uniformly mixed solution, and then adding citric acid monohydrate complexing agent in a molar ratio of lanthanum ion = 1:0.9, stirring for 2 hours to obtain a uniform mixed solution;

[0052] Step 2: Transfer the mixed solution into a water bath at 80°C and stir until a stable sol-gel precursor is formed;

[0053] Step 3: Place the sol-gel precursor in a muffle furnace, heat it to 180°C at 3°C / min, and calcine it for 1 hour, then heat it to 700°C at 3°C / min, and calcine it for 8 hours. After cooling, the catalyst La is obtained. 0.9 Ce 0.1 Co 0.1 Mn 0.9 O3.

[0054] Example 2

[0055] The improvement was made on the basis of Example 1, except that the molar ratio of La, Ce, Co and Mn metal ions was 0.9:0.1:0.4:0.6, and the other steps were exactly the same as those in Example 1. 0.9 Ce 0.1 Co 0.4 Mn 0.6 O3.

[0056] Example 3

[0057] The improvement was made on the basis of Example 1, except that the molar ratio of La, Ce, Co and Mn metal ions was 0.9:0.1:0.2:0.8, and the other steps were exactly the same as those in Example 1. 0.9 Ce 0.1 Co 0.2 Mn 0.8 O3.

[0058] Example 4

[0059] Preparation of zinc metal air battery, including:

[0060] (1) Weigh 1 mg La using an electronic analytical balance 0.9 Ce 0.1 Co 0.1 Mn 0.9 O3 powder, weighing 1 mg Super P, was ultrasonically dispersed into a mixed solution of 10 μL 5 wt% nafion solution and 190 μL ethanol, and ultrasonicated for 30 min to form a uniform catalyst ink.

[0061] (2) Use a pipette to evenly apply the catalyst ink on a 2.1 cm 2 On the hydrophilic carbon paper, 1 mg cm -2 of load.

[0062] (3) The catalyst-loaded hydrophilic carbon paper and the air-permeable layer are composited as the air positive electrode, the zinc plate is used as the negative electrode, and 6MKOH is used as the electrolyte to assemble a zinc metal air battery.

[0063] Example 5

[0064] Preparation of magnesium metal air battery, comprising:

[0065] (1) Weigh 1 mg La using an electronic analytical balance 0.9 Ce 0.1 Co 0.1 Mn 0.9O3 powder, weighing 1 mg Super P, was ultrasonically dispersed into a mixed solution of 10 μL 5 wt% nafion solution and 190 μL ethanol, and ultrasonicated for 30 min to form a uniform catalyst ink.

[0066] (2) Use a pipette to evenly apply the catalyst ink on a 2.1 cm 2 On the hydrophilic carbon paper, 1 mg cm -2 of load.

[0067] (3) A magnesium metal air battery was assembled by combining a catalyst-loaded hydrophilic carbon paper and an air permeable layer as an air positive electrode, a magnesium plate as a negative electrode, and 10 wt% KCl as an electrolyte.

[0068] V. Performance Analysis

[0069] 1. Microscopic morphology

[0070] like Figure 1 As shown, the catalyst prepared in Example 1 is compared with the standard card and it can be seen that the catalyst prepared in Example 1 has the same crystal structure as LaMnO3, which indicates that the material is successfully prepared and the dual element doping designed by the present invention does not damage the crystal structure of LaMnO3. The scanning electron microscope image of the catalyst prepared in Example 1 is as follows: Figure 2 As shown, it can be seen that the catalyst presents a porous dendritic structure. The porous structure provides a large amount of surface area, which means that more active sites can be used for electrochemical reactions, thereby helping to improve the activity and efficiency of the catalyst; the high surface area is conducive to the diffusion of reactants such as oxygen, thereby increasing the reaction rate. The porous structure allows oxygen to diffuse more easily to the catalyst surface, reducing mass transfer resistance, which is crucial for the oxygen reduction reaction (ORR) in metal-air batteries; moreover, the generated products such as water or hydrogen peroxide can also be discharged more smoothly from the catalyst surface to avoid blocking the active sites. This porous structure also provides the catalyst with good mechanical stability, can withstand stress changes during battery operation, reduce the detachment or breakage of the catalyst, help to extend the service life of the catalyst, and reduce performance degradation. More importantly, the interconnected channels in the porous structure contribute to the rapid transmission of electrons, thereby improving the overall conductivity of the electrode. The efficient electron transmission path can reduce ohmic losses and improve the energy efficiency of the battery; at the same time, the porous structure helps to evenly distribute the current density, reduce the formation of local hot spots, thereby inhibiting harmful side reactions, and ultimately keeping the byproduct H2O2 yield below 0.23%.

[0071] 2. Performance Testing

[0072] The catalyst (La 0.9 Ce 0.1 Co0.1 Mn 0.9 O3) After the powder is carefully ground, 1 mg is weighed with an electronic analytical balance, and 1 mg Super P is weighed and ultrasonically dispersed into a mixed solution of 20 μL 5wt% nafion solution, 20 μL isopropanol, and 160 μL anhydrous ethanol. Ultrasonication is performed for 30 minutes to form a uniform catalyst ink. 19 μL of catalyst ink is taken in batches with a pipette and evenly dropped on the pre-polished glassy carbon electrode (with a platinum ring) to evenly spread the suspension and cover the entire electrode. It is dried naturally at room temperature to obtain a loading of 0.384 mg cm -2 Catalyst thin film electrode.

[0073] The oxygen reduction electrochemical performance of the catalyst prepared in Example 1 was tested in a three-electrode system using a CHI760E electrochemical workstation. The working electrode was a rotating disk electrode loaded with the catalyst, the reference electrode was a Hg / HgO electrode, the counter electrode was a carbon rod, and the electrolyte was a 0.1 mol / L KOH solution. The potential was calculated according to the Nernst equation (E RHE =E Hg / HgO +0.0591×pH+0.098) was calibrated as the reversible hydrogen electrode potential (RHE). Before the test, high-purity O2 was introduced into the electrolytic cell to obtain a gas-saturated electrolyte. During the test, high-purity O2 was continuously introduced at an appropriate flow rate to keep the electrolyte saturated with gas O2.

[0074] Performance test of metal air battery:

[0075] Using 10mV s -1 The polarization curve of the battery was recorded on the electrochemical workstation at a scan rate (high-purity O2 was continuously introduced at an appropriate flow rate throughout the test to keep the electrolyte saturated with gas O2), and then the discharge curve of the battery was tested on the Xinwei battery tester.

[0076] First, multiple cycles of CV scanning were performed to activate the electrode at a scanning rate of 10 mV s -1 , the scanning voltage range is 0~1.2V, the result is as follows Figure 3 As shown, the LSV polarization curve was then tested at a rotation speed of 1600 rpm and a scan rate of 10 mV s -1 , the scanning voltage range is 0~1.2V. Figure 3 It's La 0.9 Ce 0.1 Co 0.1 Mn 0.9 The stable open circuit voltage of the O3-based primary zinc-air battery for 1000s is 1.5V, which is comparable to that of the Pt / C-based primary zinc-air battery. Figure 3It can also be seen that the voltage of the zinc metal air battery of Example 4 drops slightly in the first few hundred seconds, which may be due to the activation process or initial structural adjustment inside the battery; after more than 600 seconds, the voltage remains relatively stable, indicating that the battery has good long-term stability under this condition. This shows that the battery can maintain stable output performance under long-term operation.

[0077] Figure 4 The discharge polarization curve and corresponding power density curve of the zinc-air battery assembled with the catalyst prepared in Example 1 show that La 0.9 Ce 0.1 Co 0.1 Mn 0.9 O3-based primary zinc-air battery has 130 mW cm -2 The maximum power density.

[0078] Figure 5 The catalyst La prepared in Example 1 0.9 Ce 0.1 Co 0.1 Mn 0.9 The stable open circuit voltage of the O3-based primary magnesium-air battery after 1000s is 1.85V, which is higher than the stable open circuit voltage of the commercial Pt / C-based primary magnesium-air battery after 1000s (1.79V).

[0079] Figure 6 The discharge polarization curve and the corresponding power density curve of the magnesium-air battery assembled with the catalyst prepared in Example 1 are shown. 0.9 Ce 0.1 Co 0.1 Mn 0.9 O3-based primary magnesium-air battery has a high performance of 52 mW cm -2 The maximum power density of Mg-air batteries is shown in Figure 2, reflecting its promising prospects in magnesium-air batteries.

[0080] In summary, the catalyst of the present invention improves the catalytic performance of oxygen reduction reaction in metal-air batteries, and the limiting diffusion current density is 1.2 times that of commercial Pt / C. The maximum power densities of primary and secondary zinc-air batteries prepared based on the catalyst of the present invention are 130 mW cm -2 and 83 mW cm -2 , which is comparable to that of Pt / C-based zinc-air batteries; the assembled primary magnesium-air battery, with 3.5wt% NaCl as the electrolyte, has an open circuit voltage of 1.77V, which is higher than the open circuit potential of the Pt / C catalyst, and a maximum power density of 52mW cm -2 , which has potential commercial application value.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.

Claims

1. A perovskite-type lanthanum manganate bimetallic doped catalyst, characterized in that: The molecular formula of the catalyst is La 0.9 Ce 0.1 Co x Mn 1-x O3, wherein x is a non-negative real number and 0≤x≤0.4; the catalyst can be used as a catalyst for a metal-air battery.

2. The catalyst according to claim 1, characterized in that The catalyst is La 0.9 What 0.1 MnO3、La 0.9 What 0.1 Co. 0.1 min 0.9 O3、At 0.9 What 0.1 Co. 0.2 min 0.8 O3、At 0.9 What 0.1 Co. 0.3 min 0.6 O3、At 0.9 What 0.1 Co. 0.4 min 0.6 O3.

3. A method for preparing a perovskite-type lanthanum manganate bimetallic doped catalyst, characterized in that: The catalyst according to any of claims 1 to 2 is prepared by the following steps: Step 1: prepare salt solutions corresponding to La, Ce, Co and Mn respectively, and mix them; then add citric acid and mix evenly to obtain a mixed solution, and continuously stir the mixed solution at 50-80° C. to obtain a precursor; wherein the molar ratio of La, Ce, Co and Mn metal ions is 0.9:0.1:x:(1-x), x is a non-negative real number, and 0≤x≤0.4; the molar ratio of citric acid to the salt corresponding to La is 1:(0.8-1); Step 2: calcining the precursor prepared in step 1 at 150-180° C. for 0.5-2 h, and then calcining at 700-900° C. for 6-10 h to obtain the catalyst.

4. The preparation method according to claim 3, characterized in that: In step 1, the salt solution is one of nitrate, acetate or chloride.

5. The preparation method according to claim 4, characterized in that: The salt solution is a nitrate solution; the salt solutions corresponding to La, Ce, Co and Mn are La(NO3)3·6H2O solution, Ce(NO3)3·6H2O solution, Co(NO3)2·6H2O solution and Mn(NO3)2·4H2O solution respectively.

6. The preparation method according to claim 3, characterized in that: In step 2, the heating rate during calcination is 3°C / min.

7. A metal-air battery, characterized in that: The positive electrode catalytic material in the battery is the catalyst described in any one of claims 1 to 2 or the catalyst prepared by the preparation method described in any one of claims 3 to 6.

8. The metal-air battery according to claim 7, characterized in that: The battery is a zinc / magnesium-air battery.

9. The metal-air battery according to claim 8, characterized in that: In the battery, the catalytic electrode comprises a positive electrode catalytic material, a conductive carbon material, a nafion solution, anhydrous ethanol, a hydrophilic carbon paper and an air diffusion layer.